(untitled) (Bangladesh Journal of Botany, 2018)
A study of the response of the bud population in bamboo forests to intensive human disturbance revealed the regulation potential of the bud bank for the regeneration of bamboo populations under mulching cultivation. Differences in bud bank composition and budflow characteristics of Phyllostachys praecox Z. D. Chu et C. S. Chao ‘Prevernalis’ S. Y. Chen et C. Y. Yao were compared to explore the impact of highly intensive management on the characteristics of bamboo forest bud populations under different mulching cultivation periods. The results indicated that the soil depth at which the bud bank of bamboo forests grew decreased significantly due to intensive management during mulching cultivation. The longer the mulching time, the smaller the total number of buds, the greater the bud mortality, and the weaker the bud-input and bud-output abilities. After long-term mulching, the rates of bamboo forest bud-storage and bud dormancy decreased, output and mortality rates increased, and the bud-input rate increased, although the maximum bud-input rate was smaller than that for un-mulched areas. It was found that mulching cultivation of bamboo forests broke rhizome lateral-bud dormancy, resulting in high-intensity bud-output. Therefore, restoration of declining bamboo populations demands the increase of bud-input and the reduction of bud-output, in order to promote sustainable management of bamboo forests.